2004
DOI: 10.1002/sce.20005
|View full text |Cite
|
Sign up to set email alerts
|

Teaching future K‐8 teachers the language of Newton: A case study of collaboration and change in university physics teaching

Abstract: This interpretive case study describes a collaborative project involving a physics professor and a science educator. We report what was learned about factors that influenced the professor's development of teaching strategies, alternative to lecture, that were intended to promote prospective teachers' meaningful learning and their use of canonical ways of communicating physics concepts. We describe how the professor's beliefs influenced the pedagogy that he used to communicate the language of physics and the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The current findings support the small number of studies pointing to the need for instruction for conceptual understanding in physics (e.g., Taconis, Ferguson-Hessler, & Broekkamp, 2001). In practice, however, most physics problems assigned for homework, administered on assessments, and presented at both the high school and college level focus students on manipulating equations to solve for a single unknown quantity, and little emphasis is placed on the underlying concepts (Briscoe & Prayaga, 2004; Kang & Wallace, 2005). Instructors should tailor their curriculum and instruction so that a strong conceptual understanding of the material is stressed.…”
Section: Discussionmentioning
confidence: 99%
“…The current findings support the small number of studies pointing to the need for instruction for conceptual understanding in physics (e.g., Taconis, Ferguson-Hessler, & Broekkamp, 2001). In practice, however, most physics problems assigned for homework, administered on assessments, and presented at both the high school and college level focus students on manipulating equations to solve for a single unknown quantity, and little emphasis is placed on the underlying concepts (Briscoe & Prayaga, 2004; Kang & Wallace, 2005). Instructors should tailor their curriculum and instruction so that a strong conceptual understanding of the material is stressed.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been found that hands‐on, inquiry‐based, and interactive physics instruction is more effective than traditional instruction in helping students to resolve misconceptions (e.g., Coletta & Phillips, 2005; Hake, 1998, 2002), traditional physics instruction is the most common type of instruction still found in high school, as well as college level physics courses (Barrett, 2009; Briscoe & Prayaga, 2004; Wieman & Perkins, 2005). This is particularly true of large‐enrollment, introductory‐level college physics courses typical in many university settings (Briscoe & Prayaga, 2004; Wieman & Perkins, 2005). Given this, the goal of the present study was to understand how learner characteristics interact in a traditionally taught, large‐enrollment, introductory‐level college physics course as students' construct their understanding of physics.…”
mentioning
confidence: 99%
“…Therefore, adopting the method of collaborative study not only can eliminate the pressure on students, but can also benefit students by gathering opinions from various sources. Many studies have also documented that students become more active learners, upon interacting with teachers or peers within a collaborative learning environment (Briscoe & Prayaga, 2004; Gijlers & de Jong, 2005; Keys, 1996; Palincsar, Anderson, & David, 1993). The issue of how scientific knowledge is constructed in some way sheds light on how knowledge is negotiated or co‐constructed in social settings.…”
mentioning
confidence: 99%